Analisis Ancaman Penipuan yang Terjadi pada Penjual dalam E-comerce Bagi Dunia Bisnis di Tahun 2024 - Dwi Indah Oktaviani (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This research aims to investigate the experiences and protection strategies against fraud in digital business, focusing on Anafoya store that sells clothing products. The study reveals various challenges faced by sellers in dealing with fraud in the context of digital business. This study employs a qualitative approach with a case study research design through in-depth interviews. The interview results highlight several common forms of fraud, such as non-payment in COD transactions and returns of goods that do not match their condition. To address these challenges, Anafoya store has implemented proactive protection strategies, such as strengthening payment verification procedures and tightening return policies.